Antibacterial and osseointegration evaluation of silver ion-implanted orthopaedic implants - Hawi, Sara; Goel, Saurav; Caro, Jaume; Bonet, Raül; Orrit-Prat, Jordi; Endrino, Jose L.; Pearce, Oliver; Nishio, Wayne (Sage, 2025)
This study investigates the efficacy of silver ion-implanted or impregnated freeform surfaces of locking compression plates (LCPs) for orthopaedic applications, specifically targeting the prevention of surgical site infections without affecting the future removability of fracture fixation devices. Using stainless-steel LCPs as a testbed, we explored the antibacterial activity of silver-implanted LCP plates against Staphylococcus aureus as well as assessed the biocompatibility through osteoblast-like cell behaviour. Silver-ion-implanted LCPs demonstrated a 72% reduction in bacterial adhesion compared to controls (p < .01, Cohen’s d = 8.2), along with a 4.5-fold increase in the proportion of dead bacteria (p < .001, Cohen’s d = 10.6), although this efficacy was lower than that reported for similar ion dosages in the literature, likely due to the complexities of non-planar geometries. Furthermore, the silver-treated surfaces influenced osteoblast-like cells to exhibit a >60% reduction in attachment compared to untreated controls, with cells showing predominantly rounded morphology, an outcome beneficial for fracture fixation plates intended for eventual removal, as it discourages osseointegration. Our findings revealed the promising antimicrobial potential of silver ions as an excellent agent for the improved antibacterial performance of the LCP surfaces for fracture fixation, marking a departure from the traditional focus on permanent implant osseointegration. A key novelty of this work is the application of silver ion implantation to full-scale, geometrically complex orthopaedic implants, as opposed to the flat samples typically used in prior studies. The observed discrepancies between our results on freeform surfaces and theoretical predictions/experimental data from flat samples necessitate a deeper investigation into the influence of complex surface geometries. These results underscore the critical need to refine both our models and implantation processes to account for the effects of complex surface topography.
Keywords: 32 Biomedical and Clinical Sciences; 40 Engineering; 4003 Biomedical Engineering; Bioengineering; 5.3 Medical devices; Antibacterial; silver implantation; biotesting; osseointegration